Dívida pública, política fiscal e restrição externa no Brasil: 1994-2004 - Paulo Andre Camuri (2005)
This dissertation intends to analyze the Brazilian public debt evolution considering an environment marked by external turmoil, hidden liabilities and tight fiscal and monetary policies. The study is based on monthly data released by the Central Bank of Brazil during the period between August, 1994 and November, 2004. Many factors had influence on the public net debt figures in the referred period: i) hidden liabilities recognition; ii) primary budget deficits up to 1998; iii) high interest rates; iv) Brazil´s currency (Real) devaluation and v) external crashes. Through the automatic regressive vectors methodology, inferences about the Net Debt/GDP ratio are made. The Block Exogeneity/Wald Test suggests that interest rate is endogenously determined by the debt amount. Moreover, the analysis of both the variance decomposition and the stimulus and reaction functions shows that public debt is influenced mainly by internal shocks and that external turmoil has relevant impacts on its growth.